Explaining Germany's exceptional recovery (London, 2018)
"What explains Germany‘s exceptional recovery from the sick man of Europe in the 1990s to the powerhouse of today? Based on research of leading economists and political scientists in Europe and the US, this eBook explores the conditions leading to Germany’s rise."